Types and outcome of patients with acute poisoning presenting to emergency department of Patan Hospital, Nepal - Maharjan, Kripa; Tiwary, Abhishek; Chhetri Budhathoki, Arpana (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Poisoning poses major health and health related issues with the burden of mortality and morbidity in people. Pesticides ingestion poses major burden in our part of world whereas carbon monoxide, prescribed medication overdose is more common in developed regions. This study aimed at finding the type and outcome of patients with poisoning landing in emergency room of Patan Hospital. Method: This is a retrospective observational study conducted at Patan Hospital. This study included data of patients with acute poisoning over a period of 3 years from Apr 2020 to Apr 2023, which was obtained from the nursing register books and record section. The data included information regarding demographic profile of the patient (age and sex), type of poison and outcome of the patient namely admission, referral and mortality. Result: A total of 189 cases of acute poisoning were included in the study over a period of 3 y. Female outnumbered the male with female: male ratio of 1.14:1; 90(47.61%) were seen in age group between 18-29 y. Out of them 112(59.26%) were admitted whereas 70(37.04%) were referred and 7(3%) had mortality. Organophosphate poisoning was the most common form of poison used by the patients 116(61.38%). Conclusion: Pesticides are the most common cause of acute poisoning. Most of the cases were admitted and managed in hospital, however it still poses risk of death. Early identification of the type of poisoning will help in prompt diagnosis, standard management and patient safety.